Construção colaborativa de um serviço de Gerenciamento da Terapia Medicamentosa no Sistema Público de Saúde - Grazielli Cristina Batista de Oliveira (2018)
Pharmaceutical Care (PC) is the practice in which the pharmacist takes responsibility for attending all of a patients drug-related needs, positioning the patience at the center of the service, using a standardized method and taking responsibility for the results of his actions. Comprehensive Medication Therapy Management (CMM) is the clinical service offered in the daily life of the professional and reflects the fundamental components of Pharmaceutical Care Practice. This study describes the implementation and systematization of CMM services in the City of Lagoa Santa/MG, Brazil. In collaboration with pharmacists and the multidisciplinary health team. To this end, we used Action Research, a qualitative methodology that allows us to know and understand what happens to people and their working processes, helping them to explore their experiences and increase their understanding of their own situations. The research was conducted between Abril 2013 and August 2015, involving ten pharmacists. Fortnightly thematic discussions were held to enable engagement and critical reflections of professional about the construction of their clinical practices. The data collection methods were participant observation with field journals, document analysis, semi-structured interviews, group meetings among pharmacists and two focus groups. Data analysis was performed by looking for meaning units and categories. The results of this thesis are presented in the format of three manuscripts: the first one presents the restructuring of Pharmacy Services to insert the clinical service; the second one addresses the insertion process of CMM services in primary care, and the third one studies the impact of the management approach for the insertion of the new clinical service. The need for a clear definition of roles and responsibilities of the pharmacist in primary health care was evident in the process of restructuring pharmacy services. In order to implement CMM, the following were essential factors: management support, standardization and monitoring of the clinical service, technical of professionals, effective communication among the actors involved, and respect and integration in workflows already performed in the scenario where the service was inserted. Through the adoption of a participatory management approach in the context of Pharmacy Services, it was observed that collective construction enabled pharmacists to recognize their potentials and weaknesses, as well as their ability to take responsibility for the pharmacotherapy of the patient, showing the impact of the service management model on the innovation process of pharmacists praxis.